1996
DOI: 10.1016/s0022-5223(96)70049-1
|View full text |Cite
|
Sign up to set email alerts
|

Modified fontan operation in functionally univentricular hearts: Preoperative risk factors and intermediate results

Abstract: In a high proportion of hearts with complex univentricular anatomy, associated anomalies, and borderline hemodynamics, the Fontan operation can be performed as a total cavopulmonary anastomosis with acceptable intermediate postoperative morbidity and hemodynamic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…1,9 -11 The reasons for deterioration are multifactorial, but a low pulmonary vascular resistance remains an important prognostic factor for a good functional result after the Fontan operation. 12 NO has been used to treat pulmonary endothelial dysfunction resulting from cardiopulmonary bypass after Fontan operation. 5,13 However, to our knowledge, there are no studies examining the effect of inhaled NO on pulmonary vascular resistance late after Fontan-type operations.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 -11 The reasons for deterioration are multifactorial, but a low pulmonary vascular resistance remains an important prognostic factor for a good functional result after the Fontan operation. 12 NO has been used to treat pulmonary endothelial dysfunction resulting from cardiopulmonary bypass after Fontan operation. 5,13 However, to our knowledge, there are no studies examining the effect of inhaled NO on pulmonary vascular resistance late after Fontan-type operations.…”
Section: Discussionmentioning
confidence: 99%
“…33 Fontan patients residing at moderate altitude present with worse prognosis, presumably related to an increase in pulmonary vascular resistance. 34 Khambadkone et al 3 showed that pulmonary vascular resistance was elevated late after the Fontan operation and may fall in response to inhaled NO.…”
Section: Effect Of Sildenafil On Exercise Hemodynamicsmentioning
confidence: 99%
“…Currently, there are two techniques of Fontan procedure: intra-atrial LT [20][21][22] and extracardiac conduit [23,24]. Intra-atrial tunnel is associated with an increased risk of postoperative atrial rhythm disorders due to long suture lines within the atrium.…”
Section: Discussionmentioning
confidence: 99%